Kewenangan Penetapan Kerugian Keuangan Negara Dalam Tindak Pidana Korupsi - Seleky, Adolop; Nirahua, Salmon Eliazer Marthen; Corputty, Patrick (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: The laws and regulations in force in Indonesia have given the BPK the authority to determine and determine state losses which are the basis for investigating corruption by investigating agencies, both the Prosecutor's Office and the Police. Purposes of the Research: To examine the authority of state institutions in determining losses as the basis for investigating corruption crimes. Methods of the Research: The type of research used in this paper is normative juridical research, which is also called doctrinal research. Results Originality of the Research: The results of the study indicate that the Government Internal Supervision apparatus including BPKP according to the legislation does not have the authority to determine state financial losses as the basis for investigations by investigating agencies in corruption. The results of the determination of state losses carried out by the Government Supervision Apparatus in this case the BPKP are often used as the basis for investigating criminal acts of corruption. This will raise the question of the validity of government actions carried out by the investigative apparatus, both the Prosecutor's Office and the Police in the investigation of criminal acts of corruption